Successful Management of Isolated Optic Neuritis in Acute Diseminated Encephalomyelitis: A Case Report - Arantrinita, Arantrinita; Lukisiari , Agustini (Annals of Mechnikov’s Institute, 2021)
Background: Optic neuritis is an inflammatory disease that results in demyelination of the optic nerve. Isolated Optic Neuritis in Acute Disseminated Encephalomyelitis is a rare case, this disease attacks the central nervous system. It is monophasic, and make various clinical manifestations. Early diagnosis of Isolated Optic Neuritis due to Acute Disseminated Encephalomyelitis is based on clinical manifestations accompanied by laboratory and radiological investigations. In Acute Disseminated Encephalomyelitis patient, radiological examination can shows normal result in the acute stage. This is a challenge in establishing the diagnosis of the disease. Materials and Methods: This is a case study in post-vaccine patient. Seven-year-old girl with complaints and typical clinical manifestations includes high fever, sudden decrease in vision accompanied by pain in the movement of the eyeball. Optic nerve papillary examination shows hyperemic color with firm borders, according to the results of optical coherence tomography examination. Laboratory examination showed an increase in white blood cell count and C-reactive protein value, and multiple hyperintense lesions in the subcortical temporo-parietal characteristic of Acute Disseminated Encephalomyelitis on Magnetic Resonance Imaging. Results&Discussion : Management guided by the Optic Neuritis Treatment Trial protocol accompanied by close observation showed significant clinical improvement. Conclusion: Optic neuritis in Acute Disseminated Encephalomyelitis is an acute and monophasic disease. The most common cause is inflammatory reaction to viral and molecular mimicry reactions of the vaccine component. Early diagnosis and proper management give good results and can prevent recurrence. DOI: 10.5281/zenodo.4658034